2010
DOI: 10.1155/2010/760218
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Coinfection with Chlamydia trachomatis and Neisseria Gonorrhoeae in Nova Scotia

Abstract: The N gonorrhoeae coinfection rate in males with C trachomatis may justify empirical antimicrobials; however, in females, the proportion of coinfected may not justify empirical treatment for N gonorrhoeae infection when the C trachomatis test is positive and N gonorrhoeae testing has not been performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…22 For gonorrhea, our positivity rates were 33.1% in males and 15.9% in females compared with 22% in males and 11% in females in the United States, 21 as well as compared with 2.4% in males and 0.2% in females in Canada. 22 For coinfection, our positivity rates were 10.2% in males and 10.1% in females compared with 0.9% in males and 0.1% in females in Canada.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…22 For gonorrhea, our positivity rates were 33.1% in males and 15.9% in females compared with 22% in males and 11% in females in the United States, 21 as well as compared with 2.4% in males and 0.2% in females in Canada. 22 For coinfection, our positivity rates were 10.2% in males and 10.1% in females compared with 0.9% in males and 0.1% in females in Canada.…”
Section: Discussionmentioning
confidence: 60%
“…22 For gonorrhea, our positivity rates were 33.1% in males and 15.9% in females compared with 22% in males and 11% in females in the United States, 21 as well as compared with 2.4% in males and 0.2% in females in Canada. 22 For coinfection, our positivity rates were 10.2% in males and 10.1% in females compared with 0.9% in males and 0.1% in females in Canada. 22 In general, approximately half of the adolescents who were tested positive in our study reported at least 1 symptom or sign, and the proportion of females who were symptomatic was higher than that of the males.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…and Neisseria gonorrhoeae have been described often in screening programs and clinical settings; patients with gonorrhoeae also have been reported to have a concurrent chlamydial infection in less than 1% to a high of 70% of individuals, thus demonstrating wide variation depending on the population examined. [ 14 , 15 , 16 , 17 , 18 , 19 ]. Other coinfections of relevance in urogenital contexts include genital mycoplasmas and genital ureaplasmas.…”
Section: Introductionmentioning
confidence: 99%
“…trachomatis infections (5,8,14,16), showing a wide range depending on the population examined. Although we were unable to examine our database for dual infections, a current 2-month determination showed similar prevalence rates due to dual combo testing (C. trachomatis, 2.9%; N. gonorrhoeae, 0.29%) with 48 patients infected with both.…”
mentioning
confidence: 99%